1989
DOI: 10.1161/01.str.20.9.1168
|View full text |Cite
|
Sign up to set email alerts
|

Atheromatous pseudo-occlusion of the internal carotid artery.

Abstract: Between 1978 and1988, the diagnosis of atheromatous pseudo-occlusion of the internal carotid artery was made in 34 patients by angiography. Results of noninvasive tests were abnormal in 33 of the 34 patients examined. Twenty-five patients had carotid endarterectomy, and the other nine were treated medically. Four of the 34 patients (12%) had significant complications, two related to angiography and two to surgery. Twenty-three of the 25 operated patients were seen in long-term follow-up; 19 (83%) were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
46
2
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 33 publications
(12 reference statements)
0
46
2
1
Order By: Relevance
“…1,2,4,6,[9][10][11][12][13][14][15][16][17][18][19][20]28,31,45,[47][48][49][50][51]55,59,60,62,64,68,69,71,72 Pseudo-Occlusion. The term "pseudo-occlusion" was used for cases with raised intracranial pressure by Newton and Couch in 1960.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,4,6,[9][10][11][12][13][14][15][16][17][18][19][20]28,31,45,[47][48][49][50][51]55,59,60,62,64,68,69,71,72 Pseudo-Occlusion. The term "pseudo-occlusion" was used for cases with raised intracranial pressure by Newton and Couch in 1960.…”
Section: Figmentioning
confidence: 99%
“…Images from Sekhar et al can be called "near-occlusion with full collapse." "Pseudo-occlusion" has been used for the appearance of a collapsed artery, [1][2][3][4][5][6][7][8][9]11,[13][14][15][16][17][18][19][20][45][46][47][48][56][57][58][59][60][61][62][65][66][67][68][69][70] but also quite literally when diagnosis changed from occlusion to patent after re-review (not necessarily with distal collapse. 10,12,55,63,64,81 String Sign.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, no risk of recurrent stroke was reported. 6 In 1989, O'Leary et al 7 reported that of 9 patients with near-occlusion (most likely with full collapse) who did not undergo carotid endarterectomy, 2 had an angiographic stroke and 3 had a recurrent ipsilateral stroke within 1 year. Presumably, the angiographic strokes affected further management.…”
mentioning
confidence: 99%
“…Indeed, because only approximately half (n Ϸ 8) of the near-occlusions with full collapse were observed without an operation in NASCET and ECST, and Ringelstein et al 6 did not report the risk of recurrent stroke, the risk of recurrent stroke without or before carotid endarterectomy has only been reported for approximately 27 patients. 1,3,7 Of these, 26% (7/27; 95% CI, 8%-44%) had a recurrent stroke within 1 year-ie, roughly equal to the 3-year risk of 70%-99% stenoses (but with a wide margin of error). If anything, 26% might be an underestimation because some were not followed for a full year and some were not followed from the presenting event.…”
mentioning
confidence: 99%